Gene Therapy: The Next-Generation Therapeutics and Their Delivery Approaches for Neurological Disorders - Paul, Abhik; Collins, Michael G.; Lee, Hye Young (Frontiers in Genome Editing, 2022)
Neurological conditions like neurodevelopmental disorders and neurodegenerative diseases are quite complex and often exceedingly difficult for patients. Most of these conditions are caused due to a mutation in a critical gene. There is no cure for the majority of these neurological conditions and the availability of disease-modifying therapeutics is quite rare. The lion’s share of the treatments that are available only provide symptomatic relief, as such, we are in desperate need of an effective therapeutic strategy for these conditions. Considering the current drug development landscape, gene therapy is giving us hope as one such effective therapeutic strategy. Consistent efforts have been made to develop gene therapy strategies using viral and non-viral vectors of gene delivery. Here, we have discussed both of these delivery methods and their properties. We have summarized the relative advantages and drawbacks of viral and non-viral vectors from the perspectives of safety, efficiency, and productivity. Recent developments such as clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9-mediated gene editing and its use in vivo have been described here as well. Given recent advancements, gene therapy shows great promise to emerge as a next-generation therapeutic for many of the neurodevelopmental and neurodegenerative conditions.